Spectrum reconstruction of experimentally produced nano-colloids using Mie theory - Hamid Nadjari; Hadi Movahedinejad (Exploration of BioMat-X, 2024)
Aim: Synthesis of plasmonic nanoparticles, characterization, size detection by modeling. Methods: Colloidal plasmonic gold and silver nanoparticles were prepared by laser ablation with a 1,064 nm pulsed Nd:YAG laser with equal fractional volume and then were illuminated with its 532 nm second harmonic pulse. After the illumination process, we observed 1 nm blue shift in peak position of gold colloid and 4 nm blue shift in silver colloid. We observed a variation in the dielectric function due to nanoparticle size reduction in both samples. Using micrograph, size distribution was plotted and with the help of Mie theory and size dependent dielectric function, we reconstructed absorption spectrum to best fit the experimental spectrum and we estimated 12- and 16-fold increase in the number of Au and Ag nanoparticles respectively, due to illumination. Results: We have estimated size distribution of produced nanoparticles. Conclusions: We produced silver and gold colloids with ablation of their foils in water without any surfactant, and then we fragmented the nanoparticles colloids with an intense nanosecond laser and studied the effect of illumination on peak position and size distribution of colloids.